VALUE CO-CREATION DURING TIMES OF CRISIS: A FRAMEWORK PROPOSAL - Melia, Monia (Archives of Business Research, 2016)
The aim of this paper is to provide a framework to support companies in the development of value co-creation processes (Vargo & Lusch, 2004, 2008) during a period of economic and financial crisis. Literature review on the companies’ behavior during recession time revealed that companies can survive and be profitable modifying own marketing strategy (Köksal & Özgül, 2007), increasing the R&D budget (Laperche, Lefebvre, & Langlet, 2011), investing in innovation (Archibugi, Filippetti, & Frenz, 2013; Filippetti & Archibugi 2010; Paunov, 2012) and entering profitable foreign markets (Robert, 2003). Nevertheless studies and research on value co-creation process during economic and financial crisis time lack so far. This study adopts an abductive and explorative research approach characterized by an iterative process of systematic combinations and inferences that allow theory to be informed by reality. The theoretical study and the analysis of some value co-creation experiences launched by Philips, Barilla and Kraft, allowed to frame the main drivers of the value co-creation process during a recession time and to purpose a theoretical framework to support companies to react to economic crisis and global consumption demand reduction.